The reduced graphene oxide/WO3: Sensing properties for NO2 gas detection at room temperature - Fellah, Mehmet Ferdi (Elsevier Ltd, 2021)
The use of reduced graphene oxide/(WO3)3 as a sensor for NO2 gas was investigated by Density Functional Theory method and the results were compared with the experimental data. The charge transfer has happened between the adsorbed NO2 molecule and the reduced graphene oxide/(WO3)3 structure. The HOMO-LUMO gap of the rGO/(WO3)3 structure decreased after NO2 molecule adsorption. Based on this result, it has been revealed that the reduced graphene oxide/(WO3)3 structure can be both an electronic sensor and work function sensor. The reduced graphene oxide/(WO3)3 structure assistances from a recovery time as an sensor of NO2 molecule. Subsequently, the reduced graphene oxide/(WO3)3 structure have high potential to adsorb and detect the NO2 molecule at room-temperature. These findings have been supported by an experimental study where the reduced graphene oxide-WO3 film was used for NO2 gas sensing in literature and it has been reported that at room temperature it was a good sensing material for NO2 gas.
Keywords: (WO3)3; DFT; NO2; Reduced graphene oxide; rGO; Sensor